2016
DOI: 10.1261/rna.056184.116
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin receptor mRNA interactions contributing to iron homeostasis

Abstract: The transferrin receptor is the primary means of iron importation for most mammalian cells and understanding its regulatory mechanisms is relevant to hematologic, oncologic, and other disorders in which iron homeostasis is perturbed. The 3 ′ UTR of the transferrin receptor mRNA contains an instability element that is protected from degradation during iron depletion through interactions of iron regulatory proteins (IRPs) with five iron-responsive elements (IREs). The structural features required for degradation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 30 publications
7
28
0
Order By: Relevance
“…biology. While early studies suggested that TfR1 mRNA degradation began with an endonuclease cleavage at a specific site within the IRE region (Binder et al 1994), a recent detailed study of the IRE region did not agree with these findings and described several new sequences contributing to TfR1 destabilization within the region containing IRE-B, -C, and -D (Rupani and Connell 2016). Importantly, this study also confirmed that TfR1 mRNA decay required some trans-acting factor, as TfR1 mRNA showed no evidence for autocatalytic or ribozyme activity (Rupani and Connell 2016).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…biology. While early studies suggested that TfR1 mRNA degradation began with an endonuclease cleavage at a specific site within the IRE region (Binder et al 1994), a recent detailed study of the IRE region did not agree with these findings and described several new sequences contributing to TfR1 destabilization within the region containing IRE-B, -C, and -D (Rupani and Connell 2016). Importantly, this study also confirmed that TfR1 mRNA decay required some trans-acting factor, as TfR1 mRNA showed no evidence for autocatalytic or ribozyme activity (Rupani and Connell 2016).…”
Section: Discussionmentioning
confidence: 96%
“…Some other mRNA degradation pathways, such as those initiated by endonucleases, are also sequence-specific. The recent study by Rupani and Connell (2016) granted insight into which sequences within the IRE region contribute to TfR1 mRNA instability, and may aid in developing testable hypotheses to determine the identity of additional TfR1 degradation effector molecules. In this regard, it has recently been reported that regnase-1, an endonuclease attacking Pyr-Pur-Pyr-containing stem-loops (Matsushita et al 2009;Uehata and Akira 2013), can degrade TfR1 mRNA by targeting a region located between IRE-B and IRE-C (Yoshinaga et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This response increases iron availability in iron‐poor cells. On the contrary, in iron rich cells, lack of IRP activity increases the degradation of DMT1 and TfR1 mRNAs, in which instability elements have been recently mapped , and allows the translation of mRNAs for FPN, Ft, and other proteins that utilize iron.…”
Section: Regulation Of Cellular Iron Metabolismmentioning
confidence: 99%
“…As expected, ASO(1-10) and ASO(29-39) (200 nM), but not the scrambled control ASO (200 nM), cleaved SNCA mRNA, reducing its levels by ∼50%, as measured by RT-qPCR. Addition of 0.1, 1, and 10 μM Synucleozid to cells afforded dosedependent inhibition of SNCA mRNA cleavage by ASO(1-10), which binds the sequence in and around the A bulge, with an EC 50 of 1 μM; no effect was observed with ASO (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) or the control ASO (Fig. 5B).…”
Section: Resultsmentioning
confidence: 98%
“…Considering these positive results using luciferase constructs, the endogenous levels of APP, PrP, and ferritin were measured in SH-SY5Y cells upon Synucleozid treatment. In addition, we also studied the effect of the small molecule on the transferritin receptor (TfR) as it contains an IRE in its 3′ UTR (33) and because of its role in regulating the translation of mRNAs with IREs in their 5′ UTRs (21). Mirroring the results observed using luciferase constructs, Synucleozid had no effect on protein levels of APP, PrP, or TfR ( Fig.…”
Section: Resultsmentioning
confidence: 99%